Structure and properties of Fe40Mn20Cr20Ti10Al10 high-entropy alloy fabricated by mechanical alloying and spark plasma sintering - Jain H.; Shadangi Y.; Chakravarty D.; Dubey A.K.; Mukhopadhyay N.K. (My University, 2025)
The present work deals with the synthesis of a novel Fe40Mn20Cr20Ti10Al10 high-entropy alloy (HEA) by mechanical alloying (MA) and spark plasma sintering (SPS). The mechanically alloyed HEA exhibits a dual-phase structure consisting of BCC (a = 0.287 nm; cI2) and χ-phase (a = 0.889 nm; cI58). The 40-h milled alloy was thermally stable up to 400 °C (673 K). The as-milled alloy showed the formation of FCC solid solution around 510 °C. This finding was confirmed by the DSC and ex situ XRD of various heat-treated samples. The consolidation of milled powder led to the formation of FCC phase along with retained BCC phase (major) and nanoprecipitates of χ-phase. The hardness, elastic modulus, and compressive yield stress in the SPSed samples were ~ 6.4 ± 0.2 GPa, 184 ± 5 GPa, and ~ 1900 ± 200 MPa, respectively. The SPSed sample showed appreciable failure strain under compression of ~ 6.7%. The excellent mechanical properties in the SPSed sample may be attributed to the formation of dual phase and strengthening mostly due to grain boundary, dislocation, and precipitation. This dual-phase Fe-enriched HEA seems to have great potential in high-temperature structural applications. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.